ANALYSIS OF THE INFLUENCE OF WORK COMMITMENT AND WORK DISCIPLINE ON TEACHER PERFORMANCE WITH JOB SATISFACTION AS A MEDIATION VARIABLE - Fajar Rezeki Ananda Lubis; Syaifuddin Syaifuddin; Yusniar Lubis (Gapenas Publisher, 2023)
This research aims to analyze the effect of work commitment and work discipline on teacher performance with job satisfaction as an intervening variable at SMP Dr. Wahidin Sudirohusodo Medan. Sample taken from all members of the population, namely all junior high school teachers Dr. Wahidin Sudirohusodo Medan, because the population is 49 teachers and the population is no larger than 100 teachers and has the same level of assessment. So, researchers took 100% of the population at SMP Dr. Wahidin Sudirohusodo Medan. The data used are primary data through interviews filling out questionnaires and secondary data through documentation studies. Processing data with Path analysis The results showed that partially the variables of work commitment and work discipline on teacher performance had a positive and significant effect simultaneously the effect of work commitment and work discipline has a positive and significant effect on teacher performance at SMP Dr. Wahidin Sudirohusodo Medan